Use of rhodamine B as a biomarker in a simulated oral vaccine deployment against bovine tuberculosis in white-tailed deer - Dressel, David; VerCauteren, Kurt C.; Lavelle, Michael J.; Snow, Nathan P.; Campa, Henry (Frontiers in Veterinary Science, 2024)
Free-ranging white-tailed deer (Odocoileus virginianus) in northeastern lower Michigan, (USA) are a self-sustaining reservoir for bovine tuberculosis (bTB). Farm mitigation practices, baiting bans, and antlerless deer harvests have been ineffective in eliminating bTB in white-tailed deer and risks to cattle. The apparent prevalence has remained relatively constant in deer, prompting interest among wildlife researchers, managers, and veterinarians for an effective means of vaccinating deer against bTB. The commonly used human vaccine for bTB, Bacillus Calmette Guerin (BCG), is the primary candidate with oral delivery being the logical means for vaccinating deer. We developed vaccine delivery units and incorporated the biomarker Rhodamine B before delivering them to deer to assess the level of coverage achievable. Following deployment of Rhodamine B-laden vaccine delivery units on 17 agricultural study sites in Alpena County, MI in Mar/Apr 2016, we sampled deer to detect evidence of Rhodamine B consumption. We collected a total of 116 deer and sampled them for vibrissae/rumen marking and found 66.3% (n = 77) of the deer collected exhibited evidence of vaccine delivery unit consumption. Understanding the level of coverage we achieved with oral delivery of a biomarker in vaccine delivery units to deer enables natural resource professionals to forecast expectations of a next step towards further minimizing bTB in deer.